2020
DOI: 10.1007/s10956-020-09866-0
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Laboratories in Undergraduate Science and Engineering Courses: a Systematic Review, 2009–2019

Abstract: Current technology has the capacity for affording a virtual experience that challenges the notion of a teaching laboratory for undergraduate science and engineering students. Though the potential of virtual laboratories (V-Labs) has been extolled and investigated in a number of areas, this research has not been synthesized for the context of undergraduate science and engineering education. This study involved a systematic review and synthesis of 25 peer-reviewed empirical research papers published between 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 76 publications
(112 reference statements)
0
39
1
Order By: Relevance
“…One of the problems is some students get bored. This result is different from Reeves and Crippen (2021) positive outcomes of Vlabs is to improved student motivation.…”
Section: Figure 1 Analysis Of the Cochran Q -Test Of Media Validationcontrasting
confidence: 75%
“…One of the problems is some students get bored. This result is different from Reeves and Crippen (2021) positive outcomes of Vlabs is to improved student motivation.…”
Section: Figure 1 Analysis Of the Cochran Q -Test Of Media Validationcontrasting
confidence: 75%
“…Comparison between different types of resources and activities have identified positives for example in terms of pre-class content delivery and virtual laboratory learning (Hu-Au & Okita, 2021). Prior to the pandemic, a systematic review of virtual laboratories in science and engineering courses revealed that positive outcomes were often linked to novelty rather than pedagogical design improving student motivation (Reeves & Crippen, 2021). The emphasis on practicalbased classes in STEM disciplines can increase the complexity of BL implementation (Bernard et al, 2014), which can be further compounded by the variability in the effectiveness of teaching innovations across different STEM disciplines (Ruiz-Primo et al, 2011).…”
Section: Blended Learning In Stem Coursesmentioning
confidence: 99%
“…Researchers have emphasised the need for evaluation feedback loops to be integrated into any teaching using VAR, in order to facilitate improvement (Portman et al, 2015). Evaluations need to be designed that assess competencies of both the cognitive outcomes (knowledge and understanding) and the non-cognitive outcomes (motivation, social interactions and cognitive loads), with reference to student's individual background and learning styles (Reeves & Crippen, 2020).…”
Section: Student Learning Experiencementioning
confidence: 99%
“…This is especially important as there are a large range of teaching pedagogies that can be used with VAR technology (Grivokostopoulou et al, 2020). VAR technology on its own does not ensure positive learning outcomes (Reeves & Crippen, 2020). A review of 25 virtual laboratory studies in engineering and science reported that 13 studies concluded that there were no effects or negative effects on students learning outcomes (Reeves & Crippen, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation